The importance of native and exotic plant identity and dominance on decomposition patterns in mountain woodlands of central Argentina - Furey, Carolina (2012)
Exotic species can have a strong influence on ecosystem processes, especially when exotic invaders differ from natives in key morpho-functional features. We explored whether exotic species, especially those forming monospecific patches in Chaco montane woodlands, differ from natives in leaf attributes and decomposability. We then evaluated how exotic monospecific patches in that region alter litter decomposability, by weighting leaf trait values and decomposability by species abundance in the communities. In general, native and exotic species from Córdoba Chaco montane woodlands did not differ in leaf attributes (specific leaf area, leaf toughness, and leaf water content), or decomposability. Because of similar trait values and decomposability, we expected to find no differences in litter decomposability between plots dominated by exotic species and those of Native woodland. However, individual species decomposability weighted by species abundance in the communities showed that litter from exotic monospecific plots had slower decomposition than native ones. This pattern was confirmed by the higher decomposability and higher quality of the naturally mixed litter collected from native plots, compared to those collected from exotic plots. Despite the general similarities between most native and exotic species inhabiting Chaco montane woodlands, the overwhelming dominance of some exotic invaders in monospecific stands (and the consequent weight of their attributes on the litter each woodland produces) might be driving differences in decomposition patterns between woodland types. Our results indicate that when estimating the impact of exotic species on ecosystem processes, we should include their relative abundance in the community, as well as the relevance of the traits influencing those processes. Otherwise, we may draw erroneous conclusions.